Microencapsulated iron in food, techniques, coating material, efficiency, and sensory analysis: a review - Muñoz-More, Henry Daniel; Nole-Jaramillo, Juliana Maricielo; Valdiviezo-Marcelo, Jaime; Espinoza-Delgado, Milagros del Pilar; Socola-Juarez, Zury Mabell; Ruiz-Flores, Luis Alberto; Espinoza-Espinoza, Luis Alfredo (Frontiers in Sustainable Food Systems, 2023)
Iron deficiency in children and vulnerable people requires the intervention of effective emerging technologies to incorporate minerals into food, iron is an important micronutrient required by the human body to develop different functions. It`s oxidation and susceptibility when added directly to food hinders its absorption, impairs sensory aspects, causing rejection by consumers. Currently, efficient, low cost, high productivity, better bioaccessibility and bioavailability, microencapsulation techniques have been developed. This review focuses on the study of the different methods and techniques of iron microencapsulation and its behavior in food fortification. The type of coating material, the efficiency, yield, bioaccessibility and bioavailability evaluated for each technique. It has been shown that the most used coating materials were maltodextrin, sodium alginate, gum arabic and whey protein; while the morphological characteristics and the release profile studied from 1995 to the present, on average were in the following order: Percentage of microencapsulation (85%), yield (76%), bioavailability (60%) and bioaccessibility (52%). ; However, the sensory evaluations of some foods fortified with iron microcapsules denoted a metallic taste, color and smell were also detected, decreasing their level of acceptance. These findings suggest the need for further research to establish new protocols to fortify foods while maintaining their nutritional and sensory quality.